COVID-19 Vaccine Perception in Liver Transplant Recipients: Patient-Reported Outcomes and Real-Life Experience from the Bergamo Center - Alessandro Loglio; Elisa Farina; Francesco Ideo; Giovanni Alfieri; Tiziana Negri; Flavia Neri; Valentina Zuccaro; Stefano Fagiuoli; Stefania Camagni; Mauro Viganò (Vaccines)
Background: Bergamo was the most severely affected Italian province at the onset of the 2020 COVID-19 pandemic. The liver transplant (LT) patient population should be among the more sensitized to the concept of health prevention. Long-term data on both perception and outcomes of SARS-CoV-2 vaccination in LT recipients since the COVID-19 vaccine became available in Italy are still lacking. Methods: From May to October 2023, a survey on actively followed LT recipients at our institution was carried on by the local patient’ advocacy (Associazione Amici del Trapianto di Fegato) to define the rate of vaccinated subjects, SARS-CoV-2 infections and self-reported COVID-19-related outcomes. Results: Out of the consecutive 753 adult LT recipients invited to the survey, 356 responded (47.3%) [71% male, 63 years old (20–85), LT performed a mean of 9 years (1–26) before vaccination] and were included in the analysis. All patients received the first vaccine dose between December 2020 and January 2022 (81.7% Cominarty®, 17.7% Spikevax®, 0.3% Vaxzevria® and 0.3% Jcovden®). In the following years, adherence to the vaccination policy decreased progressively over time: the second, third, fourth, and fifth vaccine doses were administered to 99%, 94%, 72%, and 22% of the LT population by October, 2023. In total, 43 (12%) and 93 (26%) patients reported a COVID-19 episode before and after [13 (7–21) months] the first vaccination, respectively; none of the LT recipients reported a second COVID-19 infection after the following vaccination cycles. Forty-six (13%) reported short-term post-vaccination mild adverse events but none developed either acute or chronic rejection episodes or hospitalization for COVID-19-related symptoms. A total of 64% of LT recipients resulted positive for anti-nucleocapsid serological test in 2023. Conclusions: COVID-19 vaccines are safe and effective in LT recipients, underlining once again the importance of vaccination in this special population at higher risk of complications from communicable infectious diseases.